1981
DOI: 10.1139/v81-397
|View full text |Cite
|
Sign up to set email alerts
|

Quantum yields in the photolytic oxidation of some sulphur compounds

Abstract: . Can. J. Chem. 59,2750Chem. 59, (1981.The photolytic oxidation of methyl mercaptan, dimethyl sulphide, and dimethyl disulphide was studied in a batch photolysis apparatus. Short wavelength ultraviolet light was provided by a deuterium discharge lamp and monitored by a monochromator equipped with an extended response photomultiplyer tube. Sulphide concentrations were determined using a gas chromatograph equipped with a flame photometric detector having a sulphur response at 365 nm.The rate of photo-oxidation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

1983
1983
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 4 publications
1
13
1
Order By: Relevance
“…The DMS-d 6 molecules in the present experiments were cooled in a free jet under similar conditions as ICD 3 . Therefore, we can rule out the possibility that the population of high K levels in the largest N′′ states of the nascent CD 3 that originated in the photodissociation of DMS-d 6 emerges from the conservation of the initial rotation of the methyl group in the parent molecule, as found previously for warm ICD 3 prepared in an effusive leak.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The DMS-d 6 molecules in the present experiments were cooled in a free jet under similar conditions as ICD 3 . Therefore, we can rule out the possibility that the population of high K levels in the largest N′′ states of the nascent CD 3 that originated in the photodissociation of DMS-d 6 emerges from the conservation of the initial rotation of the methyl group in the parent molecule, as found previously for warm ICD 3 prepared in an effusive leak.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we can rule out the possibility that the population of high K levels in the largest N′′ states of the nascent CD 3 that originated in the photodissociation of DMS-d 6 emerges from the conservation of the initial rotation of the methyl group in the parent molecule, as found previously for warm ICD 3 prepared in an effusive leak. 16 E. Vibrational Excitation of CD 3 . In a recent experiment in our group on the photodissociation of CH 3 SCH 3 at 227.5 nm, 8 CH 3 products with up to four quanta of vibrational excitation in the ν 2 "umbrella" mode were detected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From this it was concluded that the reaction between CH3S and 02 is very slow, if it occurs at all. Sheraton and Murray [42] studied the photooxidation of CH3SH, CH3SCH 3, and (CH3S) 2. With CH3SH, they found (CH3S) 2 and SO 2 as the major products, contrary to the findings of Graham and Sie [41] who found small amounts of SO 2.…”
Section: Vlll Reaction Of Ch3s With 02mentioning
confidence: 99%
“…The ultraviolet (UV) absorption spectra of DMDS show two bands with maxima at 250 and 195 nm 5,. 6 The first band has been attributed to the promotion of a nonbonding electron from sulfur to an antibonding orbital localised in the S‐S bond (n S → σ* S−S transition). The second band at 195 nm has been assigned to n S → σ* S−S as well as n S → σ* C−S transition.…”
mentioning
confidence: 99%